Air pollution characteristics and their relation to meteorological conditions during 2014–2015 in major Chinese cities. (April 2017) - He, Jianjun; Gong, Sunling; Yu, Ye; Yu, Lijuan; Wu, Lin; Mao, Hongjun; Song, Congbo; Zhao, Suping; Liu, Hongli; Li, Xiaoyu; Li, Ruipeng
Abstract: In January 2013, the real-time hourly average concentrations of six pollutants (CO, NO2, O3, PM10, PM2.5 and SO2 ) based on data from air quality monitoring stations in major Chinese cities were released to the public. That report provided a good opportunity to publicise nationwide temporal and spatial pollution characteristics. Although several studies systematically investigated the temporal and spatial trends of pollutant concentrations, the relation between air pollution and multi-scale meteorological conditions and their spatial variations on a nationwide scale remain unclear. This study analysed the air pollution characteristics and their relation to multi-scale meteorological conditions during 2014–2015 in 31 provincial capital cities in China. The annual average concentrations of six pollutants for 31 provincial capital cities were 1.2 mg m −3, 42.4 μg m −3, 49.0 μg m −3, 109.8 μg m −3, 63.7 μg m −3, and 32.6 μg m −3 in 2014. The annual average concentrations decreased 5.3%, 4.9%, 11.4%, 12.0% and 21.5% for CO, NO2, PM10, PM2.5 and SO2, respectively, but increased 7.4% for O3 in 2015. The highest rate of a major pollutant over China was PM2.5 followed by PM10, O3, NO2, SO2 and CO. Meteorological conditions were the primary factor determining day-to-day variations in pollutant concentrations, explaining more than 70% of the variance of daily average pollutant concentrations over China. Meteorological conditions in 2015 were more adverse for pollutant dispersion than in 2014, indicating that the improvement in air quality was caused by emission controls. Graphical abstract: Highlights: The concentrations decreased 5%, 5%, 11%, 12% and 22% for CO, NO2, PM10, PM2.5 and SO2 respectively, while increased 7% for O3 in 2015. The meteorological conditions explained more than 70% of the variance of pollutant concentrations basically over China. The improvement of air quality in 2015 is caused by strict emission control. Abstract : The air pollution and its relation to meteorology over China were studied. Meteorology was adverse in 2015, implying the improvement of air quality was related to emission controls.